Acute Hemiparesis in a Child as a Presenting Symptom of Hemispheric Cerebral Proliferative Angiopathy. (12th February 2013) - Gold, J. J.; Crawford, J. R.
Abstract : A 9-year-old girl with a several-month history of unilateral intermittent headaches presented to the hospital with worsening headaches and unsteadiness. Neurologic exam was positive for a mild right hemiparesis and right homonymous hemianopsia. Noncontrast computed tomography revealed an engorged sagittal and straight sinus with prominent cortical veins concerning an arteriovenous malformation and the patient was admitted to the pediatric intensive care unit. Computed tomography angiogram demonstrated a left hemispheric vascular malformation, without evidence of dural arteriovenous fistula on conventional angiogram consistent with a diagnosis of cerebral proliferative angiopathy. There was no evidence of infarct on magnetic resonance imaging, and the patient's symptoms were completely resolved within 24 hours. Cerebral proliferative angiopathy is a rare but important vascular malformation distinct from classic arteriovenous malformations that may present with stroke-like symptoms in childhood.